Synthesis, structural elucidation and anion binding studies of isophthalamide derivatives as potential receptor for chromate anions - Maisara Abdul Kadir; Syahirah Omar; Nur Shuhaila Haryani Abd Haris; Ramizah Ramli (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study highlights the synthesis and structural elucidation of two new isophthalamide isomers namely N,N’-1,3-bis(4-methylpyridin-2-yl)isophthalamide (4-MPI) and N,N’-1,3-bis(5-methylpyridin-2-yl)isophthalamide (5-MPI), prepared from reaction between isophthaloyl chloride with 2-amino-4-methylpyridine and 2-amino-5-methylpyridine, respectively. Their potential studies as anion receptors for chromate anions are also include in this paper. Characterization of these compounds were accomplished using common spectroscopic techniques such as Fourier Transform Infrared (FT-IR), 1H and 13C Nuclear Magnetic Resonance (NMR), UV-Vis spectrometer and mass spectrometry. FTIR analysis showed the presence of four significant peaks comprising ν(N-H), ν(C-H), ν(C=O) and δ(N-H) at range 3256-3274 cm-1, 2812-2928 cm-1, 1662-1686 cm-1 and 1533-1537 cm-1, respectively. Meanwhile, 1H NMR confirmed the presence of methyl, aromatic carbon and amide resonances at δH 2.983-2.994 ppm, 6.860-8.974 and 10.138-11.300 ppm, respectively. In the 13C NMR spectra, the appearance of methyl, aromatic and carbonyl carbon signals were determined at δC 18.45-20.59 ppm, 108.42-159.22 ppm and 167.04-167.20 ppm, respectively. UV-Vis study showed that 4-MPI and 5-MPI shows promising potential as anion receptors for chromate anions.